“Unravelling Haemoglobin Variations in Sickle Cell Disease: Patterns and Implications” (International Journal of Food and Nutritional Sciences, 2022)
Sickle cell disease (SCD) is a major gene disorder among the tribal population of central India. Fetal Haemoglobin (HbF) is the best-known genetic modulator of sickle cell anaemia, which varies dramatically in concentration in the blood of these patients. The patients with SCA display a remarkable variability in the disease severity. Hence the objective of the present study was to determine the Fetal Haemoglobin (HbF) level in SCD patients (SS), carriers (AS) and normal individuals (AA). Studied population shows the highest HbF level in SS followed by AS individuals and a slightly higher HbF level in SS individuals.